Return Migration and Entrepreneurship: Does Human Capital Matter? - Syafitri, Wildan; Setyanti, Axellina Muara; Finuliyah, Firdaus (Asia Pacific Journal of Management and Education (APJME), 2024)
Return migration is a topic of considerable interest in scholarly literature, with many studies suggesting that returning migrants can impact the economic development of their home country through capital accumulation and entrepreneurship. This study seeks to examine the entrepreneurial intentions of return migrants and the influence of formal education and training on their entrepreneurial tendencies. Utilizing data from the National Workforce Survey (Sakernas) in 2020 and employing logistic regression analysis, the study revealed that formal education tends to steer returning migrants towards the formal sector rather than entrepreneurship upon their return. Conversely, while training was found to potentially increase the likelihood of entrepreneurship, the effect was not statistically significant. Additionally, individual characteristics such as age, gender, and marital status were found to significantly influence entrepreneurial intentions, with older individuals, females, and married individuals exhibiting a higher propensity for entrepreneurship among return migrants. These findings contribute to the existing literature by highlighting that, on average, return migrants in Indonesia tend to have relatively low levels of education, and higher levels of human capital may diminish their interest in entrepreneurship.